Pengaruh Transaksi E-Commerce, Pengawasan Pajak dan Pemeriksaan Pajak terhadap Penerimaan Pajak Pada KPP Pratama Kebon Jeruk Dua - Dila Anggraini; Qotrunnada Geovany Nabillah (EkoPreneur, 2020)
This study aims to determine the effect of e-commerce transactions, tax control and tax audits on tax revenue for individual taxpayers who are registered at the Jakarta Kebon Jeruk Dua Pratama Tax Office. The research method used is quantitative research. This research uses a random sampling method (randomly), while the data collection technique is done by distributing questionnaires to 100 respondents who have been calculated using the Slovin formula. The data analysis method used is descriptive statistical test, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, determination coefficient test, t-test and f test using the SPSS version 24 data processing program. The results of the partial analysis can be concluded that there is a significant influence between the variables of e-commerce transactions and tax control on tax revenue, but there is no significant effect on tax audit on tax revenue. Based on the simultaneous analysis, it can be concluded that there is a significant influence between the variables of e-commerce transactions, tax control and tax audits on tax revenue for individual taxpayers at the Kebon Jeruk Dua Primary Tax Office.Keywords:       E-Commerce Transactions, Tax Control, Tax Audit, Tax Receipt